2017
DOI: 10.17116/jnevro20171172260-65
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of immunoglobulin free light chains at the debut of multiple sclerosis

Abstract: The use of free light chains as a laboratory marker can increase the accuracy of MS diagnosis. These markers can help indirectly assess the risk of transformation of a clinically isolated syndrome into definite multiple sclerosis within the first 2 years of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…In contrast, other studies denied a correlation between disease progression evaluated by EDSS and KFLC CSF concentration or KFLC indices [43,66,69,77,84,87]. In some studies, high KFLC CSF concentrations or KFLC indices were associated with a higher risk for CIS patients to be later diagnosed with definite MS [43,50,53,54,61,68,69,73,82,83,86,130]. In other studies, this correlation could not have been observed, and CIS patients with conversion to MS did not reveal elevated CSF KFLC [55,84,87].…”
Section: Correlation Of Flc With Brain Mri and Disability Progression In Msmentioning
confidence: 92%
See 3 more Smart Citations
“…In contrast, other studies denied a correlation between disease progression evaluated by EDSS and KFLC CSF concentration or KFLC indices [43,66,69,77,84,87]. In some studies, high KFLC CSF concentrations or KFLC indices were associated with a higher risk for CIS patients to be later diagnosed with definite MS [43,50,53,54,61,68,69,73,82,83,86,130]. In other studies, this correlation could not have been observed, and CIS patients with conversion to MS did not reveal elevated CSF KFLC [55,84,87].…”
Section: Correlation Of Flc With Brain Mri and Disability Progression In Msmentioning
confidence: 92%
“…Some studies, which investigated the utility of FLC measurement in the diagnosis of MS, empirically created cut-off values either for the absolute KFLC or LFLC concentrations in CSF, CSF/serum KFLC, and LFLC quotients (Q KFLC , Q LFLC ), CSF KFLC/IgG, and LFLC/IgG ratios or KFLC/LFLC concentration ratios to determine KFLC or LFLC positivity [4,19,20,23,33,47,48,50,[52][53][54][55][60][61][62][63][64][65][66][67][68]73,74,76,77,85,[88][89][90][91]130]. The cut-off for the CSF KFLC concentration varied between 0.103 µg/mL and 7 mg/L and a mean diagnostic sensitivity and specificity of 86% (95% confidence interval (80%, 92%)) and 91% (86%, 96%) was reached while the threshold for CSF LFLC concentration varied between 0.0175 µg/mL and 4.3 mg/L and a mean sensitivity and specificity of 67% (48%, 85%) and 82% (67%, 96%) was reported [4,19,20,23,33,47,48,50,[52][53][54][55][60]…”
Section: Kflc Threshold Values In the Diagnosis Of Msmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Nazarov, V. et al showed an association between kFLC and the degree of irreversible disability in MS patients. In particular, the authors showed that MS patients with high levels of kFLC reached disability faster than patients who had low kFLC levels, suggesting that it can be a good prognostic marker in MS [44,45]. Goffette et al studied 33 patients with clinically suspected MS and no detectable OCB and reported that 54% of them were positive for kFLC.…”
Section: Csf Diagnosticsmentioning
confidence: 99%